(untitled) (PerCursos, 2024)
This article presents part of the reflections from the post-doctoral research entitled: Gramsci’s contributions to reflection on workers’ education - philological and translation challenges, shared at the seminar organized by IGS/Italy, whose theme was Gramsci, Freire and education. The research was a dual effort, engaged in the translation of unpublished texts into Portuguese and in the articulation of Gramsci’s categories in the field of education. We have tried to identify the implications of Gramsci’s thought for the reflection on the education of workers and on the education of young and adults in Brazil, as well as to highlight the links with the current state of these writings and with the thoughts of Paulo Freire, patron of Brazilian education. It is therefore understood that the study of Gramscian categories such as subalternity, hegemony and intellectuals has repercussions on the specificity of the research that addresses the aforementioned themes. The reflection highlights the role of public schools as a space of mediation for the production of knowledge, on the training of teachers, on the "conformation" of the latter to a social project of which they are often "messengers" and "reproducers", not always considering that they can have another "social role" in the construction of another project, thus recognizing themselves in a dialectical process between imposed and dynamic conformism.